Drug interaction of levothyroxine with infant colic drops. Issue 9 (23rd July 2011) - Balapatabendi, Mihirani; Harris, David; Shenoy, Savitha D
Abstract : Infacol (Forest Laboratories UK, Kent, UK) is a widely available over-the-counter preparation used to relieve colic symptoms in neonates and infants. The active ingredient is simeticone. No drug interactions with simeticone are documented in the current summary of product characteristics. The authors report the case of an infant with confirmed congenital hypothyroidism on levothyroxine who experienced a possible drug interaction with simeticone. Despite adequate levothyroxine dosage, thyroid stimulating hormone (TSH) was high, suggesting undertreatment. Questioning revealed the child was taking Infacol drops before feeds while on levothyroxine. The colic drops were immediately discontinued and TSH promptly normalised with a reduction in thyroxine requirement to an age appropriate dosage. Drug interaction of thyroxine with simeticone has not been reported previously and is not listed in the British National Formulary for Children. Clinicians and parents need to be aware of this interaction to avoid unnecessary undertreatment and prevent potential long-term neurological sequelae.